Income Distribution in the Mirror of Height Differences, The Case of Spain: 1895-1950 - Quiroga, Gloria; Coll, Sebastian (Journal of Income Distribution®, 2000)
Changes in the differences of heights among social groups could indicate shifts in income inequality. However, they can result from other factors as well. This article discusses which factors are these and, hence, which variables should we control for before taking height differences as a proxy for income inequality. An application to Spain from late nineteenth to mid-twentieth century seems to sustain the authors’ contentions, and provide some conclusions for this country and time period. Given the scarcity of data on family incomes, this method could prove valuable for the study of the long-run evolution of income distribution in other countries. Copyright 2000 Elsevier Science Inc. All rights reserved.